Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12940-023-00992-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of maternal and neonatal PFAS concentrations: a review

Abstract: Per- and polyfluoroalkyl substances (PFAS) are used for their properties such as stain and water resistance. The substances have been associated with adverse health outcomes in both pregnant mothers and infants, including pre-eclampsia and low birthweight. A growing body of research suggests that PFAS are transferred from mother to fetus through the placenta, leading to in utero exposure. A systematic review was performed using the PubMed database to search for studies evaluating determinants of PFAS concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 189 publications
(952 reference statements)
3
9
2
Order By: Relevance
“…Differences in lifestyle, cultural, and dietary factors might explain the racial heterogeneity in PFAS concentrations. 13,31,32 We found that shellfish and fish consumption was positively associated with PFAS concentrations among both females and males, specifically for PFOS, PFNA, PFDA, and sum PFAS.…”
Section: ■ Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Differences in lifestyle, cultural, and dietary factors might explain the racial heterogeneity in PFAS concentrations. 13,31,32 We found that shellfish and fish consumption was positively associated with PFAS concentrations among both females and males, specifically for PFOS, PFNA, PFDA, and sum PFAS.…”
Section: ■ Discussionmentioning
confidence: 71%
“…The association between smoking/drinking and PFAS concentrations may be affected by confounding by lifestyles such as diet, BMI, and exercise. 13 For example, wine might be consumed with seafood, which contains high PFAS concentrations, resulting in potential spurious associations between wine consumption and higher PFAS concentrations. Indeed, white wine consumption was moderately correlated with a higher fish consumption in our data.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerns over the toxicity of PFAS were extended to in utero exposure in humans. Offspring would be at higher risk of obesity and metabolic disorders , due to disruption of the maternal metabolism and placental transfer of PFASs. ,, In animal studies, in utero exposure to PFOS disrupted maternal and intrauterine metabolism, accompanied by significant decreases in placental nutrient transport and reduced fetal weights. Our previous study demonstrated that maternal exposure to PFOS disturbed offspring energy homeostasis, increased susceptibility to dietary challenges, and caused metabolic disturbances later in life . Recent studies of the Michigan mother–infant pair’s cohort and Health Outcomes and Measures of the Environment (HOME) showed that gestational PFAS exposure was associated with offspring DNA methylation. , Animal and human epidemiological studies have suggested that PFASs alter fetal metabolic programming.…”
Section: Introductionmentioning
confidence: 99%